Aktualisasi Pendidikan Kewirausahaan: Ruang Bekal Mahasiswa dengan Keterampilan Bisnis - Mika Melliani; Defri Triadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This journal delves into the implementation of entrepreneurial education's actualization within the context of developing students' business skills. Through the exploration of effective strategies and approaches, the research aims to provide profound insights into how educational institutions can optimally equip students with relevant skills for success in the business world. The study emphasizes the importance of entrepreneurial education, seeking to uncover nuanced methods for enhancing the learning experience.The investigation navigates the dynamic landscape of entrepreneurial education, emphasizing the strategic elements essential for fostering a comprehensive understanding of business skills. By uncovering effective approaches, the research aspires to contribute valuable perspectives to the ongoing discourse on educational practices.